2020
DOI: 10.1038/s41419-020-2302-x
|View full text |Cite
|
Sign up to set email alerts
|

Nogo-A-targeting antibody promotes visual recovery and inhibits neuroinflammation after retinal injury

Abstract: N-Methyl-D-aspartate (NMDA)-induced neuronal cell death is involved in a large spectrum of diseases affecting the brain and the retina such as Alzheimer's disease and diabetic retinopathy. Associated neurological impairments may result from the inhibition of neuronal plasticity by Nogo-A. The objective of the current study was to determine the contribution of Nogo-A to NMDA excitotoxicity in the mouse retina. We observed that Nogo-A is upregulated in the mouse vitreous during NMDA-induced inflammation. Intraoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 66 publications
3
21
0
Order By: Relevance
“…We found that LPS-treated Nogo-KO BMDM expressed signi cantly decreased levels of IL-6, TNF-α, IL-1β, NF-κB, CXCL1, and CXCL2 compared with WT BMDM, whereas iNOS was not signi cantly downregulated in LPS-treated Nogo-KO BMDM compared with WT BMDM (Fig. 4c-i), as previously described [40,45]. These results suggest that Nogo-A may be involved in the activation of pro-in ammatory factors in LPS-treated WT BMDM.…”
Section: Nogo De Ciency Suppresses Expression Of Pro-in Ammatory Factsupporting
confidence: 87%
See 3 more Smart Citations
“…We found that LPS-treated Nogo-KO BMDM expressed signi cantly decreased levels of IL-6, TNF-α, IL-1β, NF-κB, CXCL1, and CXCL2 compared with WT BMDM, whereas iNOS was not signi cantly downregulated in LPS-treated Nogo-KO BMDM compared with WT BMDM (Fig. 4c-i), as previously described [40,45]. These results suggest that Nogo-A may be involved in the activation of pro-in ammatory factors in LPS-treated WT BMDM.…”
Section: Nogo De Ciency Suppresses Expression Of Pro-in Ammatory Factsupporting
confidence: 87%
“…1a). Recent research has noted that retinal excitotoxicity results in the upregulation of Nogo-A expression [40]. Our results suggest that only Nogo-A, but not Nogo-B or Nogo-C, is activated in injured muscle.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Nogo-A is a potent myelin-associated inhibitor for neuronal plasticity and axonal regeneration in the injured CNS (GrandPre et al, 2000). The study of Baya Mdzomba et al (2020) found that Nogo-A is upregulated in the retina of patients with DR. And the intravitreal injection of anti-Nogo-A antibody can improve visual function and reduce RMC-mediated inflammation after retinal injury. These data may be useful to develop new therapeutic approaches for DR or neurodegenerative diseases with an important inflammatory component.…”
Section: Nogo-a Antibodymentioning
confidence: 99%